Characteristics of Fundal Changes in Fundus Tessellation in Young Adults - Lyu, Hanyi; Chen, Qiuying; Hu, Guangyi; Shi, Ya; Ye, Luyao; Yin, Yao; Fan, Ying; Zou, Haidong; He, Jiangnan; Zhu, Jianfeng; Xu, Xun (Frontiers in Medicine, 2021)
Purpose: To explore the characteristics and associated factors of fundus tessellation, especially the alternation of choroidal thickness among different degree of tessellated fundus in young adults. Design: Cross-sectional, population-based study. Methods: A total of 796 students were included in the study and underwent comprehensive ophthalmic examinations, including anterior segment examinations and swept-source optical coherence tomography (OCT) measurements. The degree of tessellated fundus was assessed by fundus photographs applying an early treatment of diabetic retinopathy study grid to evaluate the location of fundus tessellation and then divided into five groups. The topographic variation and factors, tilted disc ratio, parapapillary atrophy (PPA), retina thickness (ReT), choroidal thickness (ChT), and subfoveal scleral thickness (SST) related to tessellated fundus were analyzed. Results: Compared to normal fundus, tessellated fundus had a lower spherical equivalent (SE) (p < 0.0001), worse best-corrected visual acuity (BCVA)(p=0.043), longer axial length (AL) (p < 0.0001), thinner retina (p < 0.0001), thinner (p < 0.0001) choroid, and thinner sclera in center fovea (p=0.0035). Among all subfields of macular and peripapillary regions, center fovea and macula-papillary region showed the most significant decrease in choroidal thickness. The proportion of fundus tessellation significantly increased with lower body weight index (BMI)(p=0.0067), longer AL (p < 0.0001), larger PPA(p=0.0058), thinner choroid (p < 0.0001) and thinner sclera (p < 0.0001). Conclusions: Eyes showed more severe myopic morphological alternation with the increasement of proportion of fundus tessellation to the center fovea, including a significant decrease in both choroid and sclera thickness. Choroidal thinning may progress most rapidly in the macula-papillary region as fundus tessellation approaches to the center fovea.